The Technical System, Clinical Application and Future Prospects of Pluripotent Stem Cells (ESC/iPSC) Mediated Nerve Regeneration - Daiyi Yang (International Journal of Biology and Life Sciences, 2026)
This review systematically outlines the technological framework and clinical applications of neural regeneration mediated by pluripotent stem cells (ESCs/iPSCs). The article first compares the fundamental differences between the two: ESCs face ethical controversies regarding their embryonic origin and challenges related to immune rejection; while iPSCs support autologous transplantation, their reprogramming process may lead to genomic abnormalities, and the presence of residual undifferentiated cells poses a tumorigenic risk. The article traces the trend of directed differentiation technologies evolving from two-dimensional culture to three-dimensional organoids and details their practical applications in diseases such as stroke, Alzheimer's disease, and spinal cord injury—particularly in spinal cord injury models, where transplanted cells have achieved long-distance axonal regeneration and circuit reconstruction. Addressing core bottlenecks currently facing the field—such as low differentiation efficiency, difficulties in functional integration, and tumorigenicity—this paper explores breakthrough pathways through cutting-edge technologies including gene editing, organoids, and AI-enabled approaches. Finally, it compares the clinical advantages and disadvantages of ESCs and iPSCs, noting that while challenges remain, the deep integration of interdisciplinary technologies is accelerating the translation of stem cell therapies into standard clinical treatments, bringing revolutionary hope to patients with neurological diseases.